Developing wellbeing at school: a study on the effects of literature on students’ mental health in the Irish Junior Cycle - Fagnani, Elena (Trinity College (Dublin, Ireland). School of Education, 2022)
The low levels of adolescents’ wellbeing are currently concerning many associations and Nations, including Ireland. In this Country, to buffer this phenomenon, the NNCA introduced in 2017 a core Wellbeing Programme in the Junior Cycle that, despite representing an important step in the direction of mental health, still demonstrates some flaws. Assuming a different perspective on the topic, this study attempted to examine if activities that are already part of the school curriculum, namely reading practices, could be employed to foster students’ wellbeing. To achieve this purpose, an online survey was created and submitted to 109 Junior Cycle voluntary students in Ireland. The data gathered in the survey were analysed to provide evidence on the correlations between reading-related school practices, reading enjoyment, and wellbeing; moreover, gender and age reading differences, students’ perspective on reading, and their book preferences were explored. While no correlation was found between reading enjoyment and wellbeing, nor between reading enjoyment and reading-related school practices, a positive significant correlation was identified between reading-related school practices and wellbeing. This finding can entail important consequences for school policies regarding wellbeing, as it sets the ground for the application of reading strategies wellbeing-oriented in the traditional school curriculum.
Keywords: Psychology of Education; Education